La comprensión lectora en el proceso de enseñanza aprendizaje de los niños (as) de cuarto año de educación básica de la Escuela “Gabriela Mistral” del cantón Pelileo, provincia del Tungurahua en el año lectivo 2019 – 2020. - Quilligana Chugcho, Diana Carolina (2020)
The purpose of this research work is to investigate and improve the teaching- learning process of reading comprehension in the fourth year students of the "Gabriela Mistral" School of Basic Education and to propose to the teachers various alternatives, activities and methodology that help improve and motivate reading in students and, what is more, promote effective learning to maintain better academic performance during the school year. To obtain data, a previous diagnosis was made through a survey, dialogue with parents, interview with the undergraduate teacher, which allowed us to detect the problem and go further into its study, and to make it feasible proposals and activities that were designed to improve reading comprehension, taking into account the interests of boys and girls. Finishing that the application of certain strategies with short and multiple-choice activities improves interest in reading either in class or at home and therefore improve their academic performance, for this reason an adequate proposal and a methodological guide are made that improve reading comprehension thus giving a solution to the problem: